Rough Stage - Jarvet, Toomas (Estonia, 2015)
Maher, a Palestinian man, former political prisoner, and electrical engineer dreams of staging a contemporary dance performance in Ramallah. In order to do so, he must deal with his disapproving family, tight budgets and cultural norms. Set in today’s most contested location, Maher’s story is a parable about a society in conflict.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films